Injection Mold Unit Design of Combined Spoon-Fork (Spork) Product - Arif Budi Wicaksono; Muchlis Muchlis (Faculty of Industrial Technology Universitas Islam Indonesia, 2021)
This research aims to design injection molding unit construction for combined spoon and fork products that are in accordance with industrial standards. The mold unit designed consists of two kinds of layouts, namely grid layout and radial layout, the combined product spoon and fork grid layout that will be used is the LKM AI 4050 moldbase standard and the radial layout spoon and fork combined product will be used is the LKM AI 6065 moldbase standard. The optimum mold construction uses a grid layout and block runner system with dimensions of 400 x 500 mm which have a clamping force of 1,587.08 kN. Examples of machines that can be used are JSW J180AD injection machines with a maximum clamping force of 1770 kN.